PENATAAN POLITIK HUKUM PEMILIHAN KEPALA DAERAH DALAM RANGKA PENGUATAN DEMOKRASI LOKAL DI INDONESIA - Firman (FH UMY 060, 2016)
PENATAAN POLITIK HUKUM PEMILIHAN KEPALA DAERAH DALAM RANGKA PENGUATAN DEMOKRASI LOKAL DI INDONESIA